The Glycine max cv. Enrei Genome for Improvement of Japanese Soybean Cultivars - Michihiko Shimomura; Hiroyuki Kanamori; Setsuko Komatsu; Nobukazu Namiki; Yoshiyuki Mukai; Kanako Kurita; Kaori Kamatsuki; Hiroshi Ikawa; Ryoichi Yano; Masao Ishimoto; Akito Kaga; Yuichi Katayose (International Journal of Genomics)
We elucidated the genome sequence of Glycine max cv. Enrei to provide a reference for characterization of Japanese domestic soybean cultivars. The whole genome sequence obtained using a next-generation sequencer was used for reference mapping into the current genome assembly of G. max cv. Williams 82 obtained by the Soybean Genome Sequencing Consortium in the USA. After sequencing and assembling the whole genome shotgun reads, we obtained a data set with about 928 Mbs total bases and 60,838 gene models. Phylogenetic analysis provided glimpses into the ancestral relationships of both cultivars and their divergence from the complex that include the wild relatives of soybean. The gene models were analyzed in relation to traits associated with anthocyanin and flavonoid biosynthesis and an overall profile of the proteome. The sequence data are made available in DAIZUbase in order to provide a comprehensive informatics resource for comparative genomics of a wide range of soybean cultivars in Japan and a reference tool for improvement of soybean cultivars worldwide.